Potensi Potensi Filtrat Buah Belimbing Wuluh (Avverhoa Bilimbi L.) Terhadap Penurunan Kadar Ammonia pada Ikan Patin (Pangasius Pangasius): Potensi Filtrat Buah Belimbing Wuluh (Avverhoa Bilimbi L.) Terhadap Penurunan Kadar Ammonia pada Ikan Patin (Pangasius Pangasius) - Tuti Alawiyah; Setia Budi; Femmy Kristiani Kartina Agun (LPPM Universitas Sari Mulia, 2023)
Background: The Barito River has been polluted by ammonia caused by the rubber factory so that the fish that live around the river are positive for high ammonia compounds. This is quite dangerous for health if you often consume fish caught from the river. The fish in question is catfish which is a type of Lawang fish. Reducing ammonia levels in fish can be done in various ways, one of which is by using natural ingredients, namely wuluh starfruit which contains saponins. Objective: To determine the potential of wuluh starfruit filtrate to reduce ammonia levels in catfish of the Lawang type. Methods: The type of research carried out is Pre Experimental design, then this research design is carried out in the form of Post test only and group design and data analysis using One way Anova and then using a sampling technique with Purposive Sampling. Results: The treatments used were concentrations of 25% , 50% , 75% and 100%. The results showed that the filtrate of star fruit wuluh can be used to reduce ammonia levels in fish. The higher the concentration, the greater the decrease in ammonia levels in fish. Conclusion: The filtrate of star fruit wuluh has the potential to reduce ammonia levels in catfish of the Lawang type with an optimal concentration of 100%.